Analysis of the development of human resources policies in health in Peru - Llanos Zavalaga, Luis Fernando (2022)
Objective: To analyze the development of human resources policies in health in Peru. Methods: Cross-sectional analysis study of Health Human Resources Policies of the Ministry of Health. To this end, various Policy documents developed in Peru were reviewed, before and after the Toronto Call to Action and its degree of implementation, through three implementation tools: controls (sticks), persuasion (sermons) and incentives (carrots). The historical analysis considered: political action, civil society response and state adaptation. Results: 11 Sector Policy Guidelines were identified (five with a human resource guideline) and two specific Policy Guidelines by Line Directions; both groups not necessarily coincident. In its implementation, mainly control and persuasion policy tools were used, as well as mixed tools. Mostly control and persuasion policy tools (as well as mixed tools) were used. Incentives included better salaries and higher scores when applying for specialty positions; however, it presented distortions as an unsatisfactory motivator. Conclusions: no State Policy in human resources was identify (long term). The policies implemented are fundamentally sticks and sermons and had limited effect, due to high staff turnover and little participation by social actors, with the consequent weakening of initiatives. Incomplete use of incentives generated boomerang-like results. The effectiveness and sustainability require, harmony and continuity between Policies, and Management appropriates, leads and finances them, the harmonization of the three tools to their full potential.